2017
DOI: 10.1021/acs.energyfuels.6b03237
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Electrical Conductivity Measurements at High Temperatures: Introduction of Apparatus and Methodology

Abstract: In this paper, the electrical conductivity measurements of four types of crude oils at reservoir conditions were carried out using an in-house-developed pressurized cell. The newly introduced apparatus has the capability of performing electrical conductivity measurements of various reservoir fluids at high-pressure, high-temperature (HPHT) conditions. The cell can be pressurized with an inert gas to be far enough above the bubble points (P b ) of crude oils. The alternate voltage (AV) cycle methodology was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In general, the relationship between crude oil electrical conductivity and temperature was exponential. 80 Similar results were reported by Rocha et al ( 2019), who employed an impedance spectroscopy method to measure the electrical conductivity of heavy and medium crude oils, and water in oil (W/O) emulsions at 30 °C and 50 °C. 81 The results revealed that an increase in temperature results in an increase in electrical conductivity.…”
Section: Electrical Properties Of Asphaltenessupporting
confidence: 81%
See 3 more Smart Citations
“…In general, the relationship between crude oil electrical conductivity and temperature was exponential. 80 Similar results were reported by Rocha et al ( 2019), who employed an impedance spectroscopy method to measure the electrical conductivity of heavy and medium crude oils, and water in oil (W/O) emulsions at 30 °C and 50 °C. 81 The results revealed that an increase in temperature results in an increase in electrical conductivity.…”
Section: Electrical Properties Of Asphaltenessupporting
confidence: 81%
“…Increased oil viscosity contributes to lower conductivity at low temperatures. In general, the relationship between crude oil electrical conductivity and temperature was exponential . Similar results were reported by Rocha et al (2019), who employed an impedance spectroscopy method to measure the electrical conductivity of heavy and medium crude oils, and water in oil (W/O) emulsions at 30 °C and 50 °C .…”
Section: Electrical Properties Of Asphaltenessupporting
confidence: 79%
See 2 more Smart Citations
“…The relationship between conductivity and temperature in many nonaqueous systems can be described by the Arrheniustype equation, 31−33 and some previous research 59,60 suggest that an Arrhenius-type conductivity−temperature dependence, shown in eq 5, can be observed with crude oils as well…”
Section: Modeling the Impedance Characteristics Of Waxy Crude Oils At...mentioning
confidence: 94%